PENGARUH KINERJA KEUANGAN DAN KEPEMILIKAN MANAJERIALTERHADAP MANAJEMEN LABA DIINTERVENING ASIMETRI INFORMASI - whittleliang hakki, tandry; Selviany; Amaliyana (Prodi Akuntansi FEB UNITOMO, 2024)
Earnings management is an activity carried out by management by interfering in the preparation of a company's financial statements for the benefit of the company or individuals. The practice of earnings management can be detected using the financial performance approach, managerial ownership, and information asymmetry. This study aims to examine the effect of managerial ownership, information asymmetry, and profitability on earnings management carried out by companies. This study took the research population from financial sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The type of data used in this study is secondary data in the form of company financial reports that are used as samples. The research method used in this study is a quantitative research method. The sample was selected using the purposive sampling method. For hypothesis testing, this study uses multiple linear regression analysis. Based on the expected research results in this study are: (1) Financial performance has a significant effect on earnings management; (2) Managerial ownership does not have a significant effect on earnings management; (3) Financial performance has a significant effect on information asymmetry; (4) Managerial ownership does not have a significant effect on information asymmetry; (5) Information asymmetry has an effect on earnings management; (6) Financial performance has an indirect effect on earnings management practices mediated by information asymmetry; (7) Managerial ownership has an indirect effect on earnings management practices mediated by information asymmetry